Relation of general-perceptual cognitive abilities and sport-specific performance of young competitive soccer players - Schumacher, N.; Zaar, C.; Kovar, J.; Lahmann-Lammert, L.; Wollesen, B. (European Journal of Sport Science, 2024)
In soccer, skill is significantly influenced by motor skills and physical constitution. In addition, perceptual-cognitive abilities are thought to affect sport-specific performance. Nevertheless, there are hardly any studies investigating the relationship of general cognitive abilities with sport-specific performance. Therefore, the aim of this study was to analyze relationships between general perceptual-cognitive abilities and soccer-specific performance in competitive youth sports. Thirty highly talented male youth soccer players aged 12-14 years completed various perceptual-cognitive (selective attention, cognitive flexibility, inhibition, working memory, peripheral perception, and choice response) and sport-specific on-field tests. Cognitive abilities were assessed using a computer-based test system. Soccer-specific performance skills were evaluated by two sport-specific on-field tests. The relation between perceptual-cognitive abilities and soccer-specific performance was examined using a correlation analysis as well as a four-stage regression analysis. Overall, the expression of general perceptual-cognitive abilities was found to have an impact on performance in soccer-specific test situations, particularly cognitive flexibility and selective attention. Our results suggest that general cognitive tests could be an important tool for the evaluation of cognitive abilities in soccer. This study brings together key approaches in expertise research and makes a significant contribution to a better understanding of expertise in soccer.